Harnessing collective radiative phenomena on a photonic Kagome lattice - Salinas, Ignacio; Cornejo, Javier Cubillos; Szameit, Alexander; Solano, Pablo; Vicencio, Rodrigo A. (APL photonics, 2024)
Photonic lattices enable experimental exploration of transport and localization phenomena, two of the major goals in physics and technology. In particular, the optical excitation of some lattice sites, which evanescently couple to a lattice array, emulates radiation processes in structured reservoirs, a fundamental subject in quantum optics. Moreover, the simultaneous excitation of two sites simulates collective phenomena, leading to phase-controlled enhanced or suppressed radiation, namely super- and subradiance. This work presents an experimental study of collective radiative processes on a photonic Kagome lattice. A single or simultaneous—in-phase or out-of-phase—excitation of the outlying sites controls the radiation dynamics. Specifically, we demonstrate a controllable transition between a fully localized profile at the two outlying sites and a completely dispersed state into the quasi-continuum. Our result presents photonic lattices as a platform to emulate and experimentally explore quantum optical phenomena in two-dimensional structured reservoirs, while harnessing such phenomena for controlling transport dynamics and implementing all-optical switching devices.